2021
DOI: 10.3389/frsc.2021.666111
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Motor Vehicle Accidents and Fatalities in Botswana-An Epidemiological Study

Abstract: According to WHO, more than 300,000 pedestrian deaths were recorded globally, accounting for 22% of total road user fatalities in 2019. In 2017, Botswana pedestrian fatalities were considerably high at 32% of the total road accident fatalities recorded. This paper investigated causes, distribution, risk, and offers potential solutions to pedestrian accidents and fatalities in Botswana. Secondary data extracted from different sources were analyzed through descriptive statistics and stepwise regression modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It could be attributed to less risk taking behavior that makes females relatively safer as drivers (Singh et al, 2016;Ambade et al, 2021). However, females are at higher risk as pedestrians because of socioeconomic standards in developing countries that make females earn less money so; female victims are more pedestrians than drivers (Ambade et al, 2021;Mphela et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It could be attributed to less risk taking behavior that makes females relatively safer as drivers (Singh et al, 2016;Ambade et al, 2021). However, females are at higher risk as pedestrians because of socioeconomic standards in developing countries that make females earn less money so; female victims are more pedestrians than drivers (Ambade et al, 2021;Mphela et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies have been applied to know the factors that cause pedestrian accidents, like survey-based questionnaires, interviews with the victims of accidents, and modeling-based approaches. But it was found that most specific factors like gender, age [13], [19], and urban areas have been studied, while rural areas have been linked with the factors of over speeding and poor infrastructure [20]. But in the present study, we are considering both human factors and vehicle-related factors that cause pedestrian road accidents while taking into account different surrounding contexts, geographical distribution, different weather conditions, daytimes, and other factors.…”
Section: Related Workmentioning
confidence: 99%
“…, 2021). Road vehicle accidents result in fatalities, disabilities and substantial financial burdens both for society and the individuals directly affected (Mphela et al. , 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Multiple elements contribute to the heightened risk of such collisions, encompassing vehicle design, operational speed, road infrastructure, environmental conditions, driver proficiency, potential impairments and driver conduct (Giummarra et al, 2021). Road vehicle accidents result in fatalities, disabilities and substantial financial burdens both for society and the individuals directly affected (Mphela et al, 2021).…”
Section: Road Accidentsmentioning
confidence: 99%